Mathematical Methods in Modern Scientific Knowledge and Mathematical Style of Thinking - Xo'jayev Allayor Maxmudjon o'g'li; Gadayev Doniyor Rajabovich (Zien Journals, 2023)
Mathematical methods in the modern theory of knowledge are considered, the possibilities of applying mathematics in various fields of science are shown.
Keywords: mathematics; philosophical problems; history of mathematics